HUBUNGAN TINGKAT KECEMASAN TERHADAP KEJADIAN NYERI PUNGGUNG BAWAH PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2021 - Aura Discyacitta Firstisha Putri, (2022)
Introduction: Since the world was shocked by the COVID-19 pandemic, to anticipate its transmission, learning activities in Indonesia were shifted into limited face-to-face or online learning methods. This change requires students to adapt to the implementation of new learning system and various problems that can cause pressure and burden on the physical and psychological conditions of medical students arise and eventually trigger musculoskeletal disorders such as low back pain and psychological disorders such as anxiety. This research had general purpose to determine the relationship of anxiety level with low back pain among medical students at UPN Veteran Jakarta in 2021. Methods: A cross-sectional method was chosen for observational analysis in this study. This study used Proportionate Stratified Random Sampling for sampling method. Data were collected using Nordic Musculoskeletal Questionnaire (NMQ), Numeric Pain Rating Scale (NPRS), and Hamilton Anxiety Rating Scale (HARS). Chi-Square test was performed for bivariate analysis. Results: The results of the statistical test among 157 respondents showed that there was significant relationship between anxiety level with low back pain (p-value = 0.030). Conclusion: The conclusion of this study can be drawn based on the results, we can conclude that anxiety level is related to occurrence of low back pain among medical students at UPN Veteran Jakarta in 2021.